Case report: Multiple brain metastases of atrial myxoma: Clinical experience and literature review - Ma, Kang; Zhao, Dawei; Li, Xuegang; Duan, Haijun; Yan, Chaojun; Wang, Shi; Zeng, Lan; Xu, Kai; Lai, Ying; Chen, Beike; Mu, Ning; Yang, Chuanyan; et al. (Frontiers in Neurology, 2023)
Myxoma is the most common type of benign cardiac tumor in adults, and it has a strong tendency to embolize or metastasize to distant organs. Patients with multiple brain metastases have rarely been seen in clinics; hence, standard treatment protocols for multimyxoma metastasis in the brain have not been established. We present the case of a 47-year-old female who had convulsions in the right hand and repeated seizures. Computed tomography revealed multiple tumor sites in her brain. Craniotomy was conducted to remove the tumor sites. However, recurrent brain tumors and unexpected cerebral infarctions occurred frequently shortly after the treatment because the cardiac myxoma had not been treated due to the patient’s personal concerns. The myxoma was resected by gamma knife radiosurgery, and temozolomide was given prior to cardiac surgery. There has been no evidence of tumor recurrence from the 2 years following the surgery until the present. This case highlights the importance of prioritizing cardiac lesions over cerebral lesions; if a cerebral metastasis has been found, it is likely that the cardiac myxoma is already unstable, with high rates of spread and metastasis. Therefore, it is unwise to treat metastasis sites before the cardiac myxoma. Additionally, the case suggests that gamma knife radiosurgery combined with temozolomide is effective as treatment for multiple myxoma metastasis in the brain. Compared with conventional cerebral surgery, gamma knife radiosurgery is safer, causes less bleeding, and requires a shorter time for recovery.